2011
DOI: 10.1007/s10286-011-0153-3
|View full text |Cite
|
Sign up to set email alerts
|

Tilt-induced cardioinhibitory syncope: a follow-up study in 16 patients

Abstract: Although syncopal recurrences were common, tilt-induced asystole did not imply a poor prognosis in terms of death or major therapeutic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
2
8
2
Order By: Relevance
“…In terms of mortality, all studies, including this study with very prolonged asystoles, are consistent with a favorable prognosis, with no reported deaths. It is worth evidencing that in the case of this study, as in other studies in adult populations, the lack of mortality occurred despite a nonaggressive treatment (no pacemaker implantation).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In terms of mortality, all studies, including this study with very prolonged asystoles, are consistent with a favorable prognosis, with no reported deaths. It is worth evidencing that in the case of this study, as in other studies in adult populations, the lack of mortality occurred despite a nonaggressive treatment (no pacemaker implantation).…”
Section: Discussionsupporting
confidence: 66%
“…Few studies have specifically addressed the prognosis of patients with reflex syncope and an asystolic response to HUT test (with asystoles over 3 seconds), but those that did were consistent with a favorable outcome, regardless of the treatment applied (pacemaker, pharmacological treatment, general measures, or no treatment; Table ) . These studies included some patients with asystoles greater than 30 seconds and a recent study by Sau et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we observed that asystole period during the cardioinhibitory response could reach 14 sec and extremely over up to 25 sec especially in adult subjects with age among 25-50. Guaraldi et al recently reported that asystole period developed during the HUTT did not lead a poor prognosis in a study population other than frequent syncope episodes in a limited number of subjects (10). Although those long asystole periods did not precede or degenerated to any undesired events in our study, we already recommended the implantation of a pacemaker with the feature of heart rate acceleration to our patients with asystole period longer than 5 sec.…”
Section: Discussionmentioning
confidence: 49%
“…Despite the benign course of vasovagal syncope, without mortality, there is recurrence of syncope in these patients with cardioinhibitory response from 9% to 62.5% during follow up 24 to 77 months [15, 17, 18, 23, 24]. An interesting observation is that heart rhythm during the episode of recurrence is identical to the first spontaneous syncope [25].…”
Section: Cardioinhibitory Vasovagal Syncopementioning
confidence: 99%